CLINICAL AND LABORATORY CHARACTERISTICS OF THE INFECTION CAUSED BY ENTEROVIRUS-71 - E. N. Simovanyan; V. B. Denisenko; L. F. Bovtalo; L. V. Belugina; M. A. Kim; Yu. S. Kuhol (LLC "Diagnostics and Vaccines", 2015)
Adverse course of enterovirus-71 infection (EVI-71) in children, frequent development of the nervous system pathology determine the need for early disease diagnosis. The study included 139 children aged 6 months to 13 years. Modern EVI-71 features is a frequent defeat of children aged from 3 to 7 years, attending organized groups, the priority development of combined moderate severity forms without nervous system pathology. EVI-71 is characterized by cyclical course, appearance in the first two disease days fever, murrain-like, catarrhal, lymphoproliferative syndromes, conjunctivitis, headaches. The second stage of the disease (3- 6 days) in 37.9% children accompanied by attaching of meningitis and meningoencephalitis symptoms (common cerebral, meningeal and encephalic syndromes, changes in cerebrospinal fluid). In the EVI-71 diagnosis must be observed epidemiological history, clinical and laboratory parameters, detection of enterovirus-71 and its RNA from feces, oropharyngeal mucus and cerebrospinal fluid. Patients with EVI-71 need for combined treatment, including causal agents and pathogenetic therapy.